Mixed-conifer forest reference conditions for privately owned timberland in the southern Cascade Range - Collins, Brandon M.; Bernal, Alexis; York, Robert A.; Stevens, Jens T.; Juska, Andrew; Stephens, Scott L. (Ecological applications, 2021)
The overwhelming majority of information on historical forest conditions in western North America comes from public lands, which may provide an incomplete description of historical landscapes. In this study we made use of an archive containing extensive timber survey data collected in the early 1920s from privately owned forestland. These data covered over 50,000 ha and effectively represent a 19% sample of the entire area. The historical forest conditions reconstructed from these data fit the classic model of frequent-fire forests: large trees, low density, and pine-dominated. However, unlike other large-scale forest reconstructions, our study area exhibited relatively low overall variability in forest structure and composition across the historical landscape. Despite having low variability, our analyses revealed evidence of biophysical controls on tree density and pine fraction. Annual climatic variables most strongly explained the range in historical tree densities, whereas historical pine fraction was explained by a combination of topographic and climatic variables. Contemporary forest inventory data collected from both public and private lands within the same general area, albeit not a direct remeasurement, revealed substantial increases in tree density and greatly reduced pine fractions relative to historical conditions. Contemporary forests exhibited a far greater range in these conditions than what existed historically. These findings suggest that private forestland managed with multiaged silviculture may be similar to public forestland with respect to departure in forest structure and compositions from that of historical forests. However, there may be differences between management objectives that favor timber production, more typical on private lands, vs. those that favor restoration, increasingly supported on public lands.